Revolusi Kesehatan dengan Inovasi Keperawatan dan Teknologi untuk Mengatasi Penyakit Tidak Menular - Ariga, Reni Asmara; Jaya, Ivan; Sufi, Al Anhar; Ariga, Selviani; Ariga, Fajar Amanah; Astuti, Sri Budi; Ariga, Hijrah Purnama Sari; Sari, Dian Maya; Karnodi, Karnodi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Non-communicable diseases (NCDs) are a global threat that requires innovative approaches in management such as the application of nursing innovation and information technology focused on health independence through WEB-based self-care methods. The main problem is the lack of accessibility of information and support needed by the community in NCD management, low healthy living behavior in NCDs. The method used was a holistic approach, designing and implementing an integrated disease management strategy, including health condition monitoring, care planning, and health education to the community, developing and maintaining a dedicated website that provides health information related to non-communicable diseases, health condition monitoring tools, as well as interactive features for the community of Kelambir Lima Village in managing their health independently. providing training to the community on how to use the website to monitor health conditions, access accurate health information, and implement steps to improve healthy lifestyles to prevent and manage NCDs. Findings showed increased community participation in personal health management, and improved understanding of health conditions. It is recommended that the integration of nursing innovation and information technology can bring about a revolution in NCD management and drive positive changes in public health.